Instructed partnership appreciation in depression: effects on mood, momentary relationship satisfaction, and stress reactivity [dataset] - Warth, Marco (Universität, 2020)
This study compared the affective and psychobiological response of depressed and non-depressed romantic couples in an instructed partnership apprec...
Gesehen am 16.07.2020
Keywords: Forschungsdaten; Datenbank